2014
DOI: 10.1097/ta.0b013e3182a900bc
|View full text |Cite
|
Sign up to set email alerts
|

Increased suicidal activity following major trauma

Abstract: Epidemiologic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…As less than six cases of assault injuries with subsequent suicidality were observed in that study, the investigators were unable to assess assault injury as a unique predictor of suicidal behavior (March et al., ). Although the association of self‐inflicted injury and unintentional injury with future risk of suicidal behavior is well characterized (Franklin et al., ; March et al., ), the risk of suicidal behavior conferred by assault injury remains relatively understudied. Nonetheless, the association between assault injury and subsequent suicidal behavior is theoretically and clinically important.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…As less than six cases of assault injuries with subsequent suicidality were observed in that study, the investigators were unable to assess assault injury as a unique predictor of suicidal behavior (March et al., ). Although the association of self‐inflicted injury and unintentional injury with future risk of suicidal behavior is well characterized (Franklin et al., ; March et al., ), the risk of suicidal behavior conferred by assault injury remains relatively understudied. Nonetheless, the association between assault injury and subsequent suicidal behavior is theoretically and clinically important.…”
mentioning
confidence: 93%
“…Nearly 45,000 people per year in the United States die by suicide (Drapeau & McIntosh, 2017), and more than 1 million people per year attempt suicide in the United States (Piscopo & Lipari, 2016). Previous scholarship has identified myriad risk and protective factors for suicidal behavior (O'Connor & Nock, 2014), 3 including traumatic injury (March et al, 2014;Stein et al, 2010). In a large study of medical inpatients in Manitoba, March et al (2014) found that patients with traumatic injuries were more than four times as likely to attempt suicide in the future compared to uninjured controls from the general population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…March et al 15 reported that adults with unintentional major traumatic injuries, indicated by total Injury Severity Scores (ISSs) >12 (combined head and extracranial ISS), have >4 times the risk of SA or completed suicide compared with the general population, even after adjusting for psychiatric conditions (anxiety/mood disorders and substance abuse), physical comorbidities, and other psychosocial factors (income and residence). Similarly, those with life-threatening physical illness (eg, TBI, stroke, myocardial infarction, spinal cord injury [SCI]) have higher rates of SI (11.3%) developing up to 2 years after illness onset, compared with the general population.…”
mentioning
confidence: 99%
“…The population-attributable risk fraction of lifetime suicide attempts for childhood trauma exposure may be as high as 67% [6]. Similarly, traumatic experiences during adulthood have been associated with suicidal behaviors [11,12]. Even after controlling for a history of childhood trauma, odds for the onset of suicidal behavior increase with adulthood traumas, such as interpersonal violence and sexual assault [12].…”
Section: Introductionmentioning
confidence: 99%